Controlled prospective randomised trial on the effects on pulmonary haemodynamics of the ambulatory long term use of nitric oxide and oxygen in patients with severe COPD. Issue 4 (1st April 2003) - Vonbank, K; Ziesche, R; Higenbottam, T W; Stiebellehner, L; Petkov, V; Schenk, P; Germann, P; Block, L H
Abstract : Background: Pulmonary hypertension is a frequent complication of severe chronic obstructive pulmonary disease (COPD) and a major cause of morbidity and mortality in this condition. Based on the improved survival of these patients due to long term oxygen therapy and the potent and selective pulmonary vasodilation by inhaled nitric oxide, the safety and effectiveness of the combined inhalation of these two gases over a 3 month period was assessed. Methods: Forty patients with secondary pulmonary hypertension due to COPD were randomly assigned to receive either oxygen alone or "pulsed" inhalation of nitric oxide with oxygen over a period of 3 months. "Pulsed" inhalation of nitric oxide was used to reduce pulmonary ventilation-perfusion mismatch and formation of toxic reaction products of nitric oxide and oxygen. Results: Compared with oxygen alone, the combined inhalation of nitric oxide and oxygen caused a significant decrease in mean (SE) pulmonary artery pressure (from 27.6 (4.4) mm Hg to 20.6 (4.9) mm Hg, p<0.001) and pulmonary vascular resistance index (from 569.7 (208.1) to 351.3 (159.9) dynes −1 cm −5 m −2, p<0.001) without decreasing arterial oxygenation. Cardiac output increased by 0.5 litres (from 5.6 (1.3) l/min to 6.1 (1.0) l/min, p=0.025). Systemic haemodynamics and left heart function remained unchanged during this period and no increase in toxic reaction products of nitric oxide was observed. Conclusions: This is the first controlled trial indicating that the "pulsed" inhalation of nitric oxide together with oxygen may be safely and effectively used for the long term treatment of severe COPD.